"Big" Sounds Bigger in More Widely Spoken Languages. Issue 11 (10th November 2021) - Lev‐Ari, Shiri; Kancheva, Ivet; Marston, Louise; Morris, Hannah; Swingler, Teah; Zaynudinova, Madina
Abstract: Larger communities face more communication barriers. We propose that languages spoken by larger communities adapt and overcome these greater barriers by increasing their reliance on sound symbolism, as sound symbolism can facilitate communication. To test whether widely spoken languages are more sound symbolic, participants listened to recordings of the words big and small in widely spoken and less common languages and guessed their meanings. Accuracy was higher for words from widely spoken languages providing evidence that widely spoken languages harbor more sound symbolism. Preliminary results also suggest that widely spoken languages rely on different sound symbolic patterns than less common languages. Community size can thus shape linguistic forms and influence the tools that languages use to facilitate communication.